Influence of propylene glycol on the tribological performance and lubrication mechanism of water-based lubricants incorporating silicon carbide, magnesium oxide and aluminium oxide nanoadditives - Azizan, Muhammad Ashman Hakimi; Sulaiman, Mohd Hafis; Yaakob, Yazid (Malaysian Tribology Society, 2025)
Water-based lubricants (WBLs) offer cooling capabilities and are environmentally friendly compared to oil-based lubricants, though they have low viscosity and can result in very thin film thicknesses. This study evaluates the effects of propylene glycol as a dispersant on the dispersion stability of various nanopowder additives, specifically magnesium oxide (MgO), aluminium oxide (Al2O3), and silicon carbide (SiC). The physical, mechanical, and tribological properties of the formulated WBLs were examined. Tribological assessments were performed using block-on-ring setup following ASTM 7798 standards under different rotational speeds and contact loadings. Results shows that addition of propylene glycol improves the viscosity of WBLs with MgO have the highest viscosity of 26.32 mPa·s compared to water alone. MgO/SiC was proven to have the lowest frictional coefficient of 0.1802, as well as lowest wear loss of 0.1118% which makes it the best lubricant in this study. The study found that combination of nanoadditives with propylene glycol is an effective solution to improve the tribological performance of lubricants which potentially led to an environmentally sustainable lubricant.